Polymicrogyria, Large Corpus Callosum and Psychomotor Retardation in Four-Year-Old Girl: Potential Association Based on MR Findings: A Case Report and Literature Review. Issue 5 (October 2014) - Budai, Caterina; Moscato, Giulia; Patruno, Francesco; Leonardi, Marco; Maffei, Monica
We describe a child from consanguineous parents presenting mega corpus callosum (MegaCC), polymicrogyria, psychomotor retardation with swallowing difficulties and language impairment perhaps linked to the syndrome of megalencephaly-polymicrogyria-mega corpus callosum (MEG-PMG-MegaCC). Reviewing the literature, we speculate that MegaCC, psychomotor retardation and anomalies in cortical migration are the three pathognomonic features. The presence of additional possibly associated anomalies such as megalencephaly, indicates that the spectrum of linked malformations with this rare syndrome is broad and yet to be defined.